Autologous cytokine‐induced killer (CIK) cells enhance the clinical response to PD‐1 blocking antibodies in patients with advanced non‐small cell lung cancer: A preliminary study. Issue 2 (4th November 2020) - Han, Ying; Mu, Di; Liu, Ting; Zhang, Huan; Zhang, Jiali; Li, Shuzhan; Wang, Rui; Du, Weijiao; Hui, Zhenzhen; Zhang, Xinwei; Ren, Xiubao
Abstract : Background: Programmed death‐1 (PD‐1) blocking antibodies have been shown to improve progression‐free survival (PFS) and overall survival in a subset of patients with non–small cell lung cancer (NSCLC). However, the objective response rate with these agents remains low, and the vast majority of NSCLC patients require alternative combination treatment regimens to prolong their survival. The purpose of this study was to evaluate the clinical efficacy of autologous cytokine‐induced killer (CIK) cell infusions combined with PD‐1 blocking antibodies in patients with NSCLC. Methods: In this preliminary study, we investigated the safety and immune function effectiveness of PD‐1 blockade antibodies pembrolizumab or nivolumab administered in combination with or without autologous CIK cell infusions in 18 patients with advanced NSCLC. The peripheral blood mononuclear cells were isolated from these patients and the expression level of some cell surface molecules like PD‐1 were detected using flow cytometry to reflect the effectiveness of this combination regimen. Results: No treatment‐related deaths occurred in either cohort. In comparison with the pretreatment level, CD3 + CD56 + CD16 + T cells were significantly increased with the combination therapy, while myeloid‐derived suppressor cells were significantly increased with PD‐1 blocking antibody therapy alone but not with combination therapy. Although the serum interleukin‐4 level was downregulated following treatment with the combination regimen, interferon‐γ levels were unchanged. Conclusions: The purpose of this clinical study was to report the clinical efficacy and lack of exacerbated autoimmune adverse events with a combination of PD‐1 blockade and CIK cell infusions in patients with advanced NSCLC, further supporting assessments of this combination in future clinical trials. Abstract : We conducted a retrospective study of PD‐1 blocking antibodies (pembrolizumab or nivolumab) plus autologous CIK cells to assess the safety, effectiveness, and influence on immune function of this treatment in a total of 18 patients with advanced NSCLC. We found that disease control rate (DCR) was significantly higher in patients who received a combination of PD‐1 blockade + CIK cell infusions than in those who received a PD‐1 blocking antibody alone. This clinical study provides data support for further clinical trials in the future.